Protective effect of Spirulina against bone fragility induced by Garcinia cambogia in high-fat diet induced obese rats - Cho, X.; Okechukwu, P. N.; Mohamed, N.; Froemming, Gabriele Ruth Anisah; Chan, H. K. (IFRJ, Faculty of Food Science & Technology, UPM., 2022)
The present work evaluated the protective effects of Spirulina against the bone fragility caused by Garcinia cambogia in high-fat diet induced obese rats. High-fat diet and high-fat emulsion (HFD+HFE) were administered via oral gavage to 30 six-week-old female Sprague Dawley rats for six weeks to induce obesity, except for a normal group (n = 6). Following four weeks of treatment, the diet-induced obese groups were orally administered, daily, with (1) G. cambogia (GC); (2) Spirulina (S); and (3) G. cambogia + Spirulina (GC+S). The normal and obese control groups were treated with equal volumes of 0.9% saline water. It was found that GC significantly decreased body mass index (BMI) below the obese range (0.68 g/cm2 ). Additionally, GC altered bone mineral density (BMD), increased phosphate and calcium levels, and decreased maximum force and mineral apposition rates (MAR) as compared to the obese control group (p < 0.05). Bone fragility caused by GC was confirmed by the decrease in bone formation marker osteocalcin (OCN), as well as an increase in bone resorption markers receptor activator of nuclear factor kappa-B ligand (RANKL) and tartrate-resistant acid phosphatase type 5b (TRAP5b) as compared to the obese control group. Spirulina also decreased the BMI of the obese rats. Spirulina also increased blood bone markers, BMD, maximum force, and Young’s modulus. Rats supplemented with GC+S demonstrated higher double-labelled surface (dLS/BS) and MAR as compared to those in the GC group (p < 0.05). Meanwhile, the S group demonstrated improvement in all dynamic histomorphometric indices. S and GC+S groups demonstrated bone formation upregulation and bone resorption downregulation, thus indicating a bone protective effect of Spirulina. Overall, GC treatment led to bone fragility. GC+S treatment significantly augmented bone formation and mineralisation in obese rats as compared to the GC treatment alone. Rats in the S group demonstrated effective weight reduction while showing no destructive effects on the bone.